Extratos do tratado sobre os princípios fundamentais para tocar violino de Leopold Mozart: tradução e análise - Silva, Lilian Maria Pereira da (2014)
This paper takes as its object of exegetical analysis, based on the translation from English to Portuguese, the treatise on the fundamental principles for violin, written by Leopold Mozart, first published in 1756. The Portuguese version was based on the English version made by Editha Knocker and edited in 1948 by the Oxford University Press. The translation into Portuguese brings the possibility of a careful and specific study of the treatise, making possible an effective and clear apprehension of the ideas about the music and the violin, proposed and supported by Leopold Mozart. The fundamental categories elaborated in that work are explained in a more substantive and understandable way, which constitutes the core of this project. That treatise is a work of undeniable historical relevance and, along with the treatise for flute by J. J. Quantz and the one for keyboard by C. P. E. Bach, is one of the most significant works of the genre. In his work, L. Mozart deals not only with the technique for the violin and musical styles, but also displays an honest concern with the musical training of instrumentalists. In his didacticism, leads the reader to study the characteristics of violinistic musical practice, as well as the string instruments with bow, from the eighteenth century to the present day.